Analysis of Magnetic Field of Electrical Devices Based on Their Circuit Models - Горячко, Всеволод; Гамола, Орест; Рижий, Тарас; Horyachko, Vsevolod; Hamola, Orest; Ryzhyi, Taras (Видавництво Львівської політехніки, 2021)
Запропоновано аналіз магнітних полів електричних машин і електромагнітних апаратів на підставі їх колових математичних моделей. Магнітні системи електротехнічних пристроїв у цих моделях подано у вигляді планарних нелінійних магнітних кіл зі зосередженими елементами. Параметри цих елементів визначено на підставі геометричних розмірів з врахуванням конструктивних особливостей пристроїв та фізичних параметрів середовища.

The article deals with an analysis of magnetic fields of electric machines and electromagnetic devices on the basis of their circuit mathematical models. The magnetic systems of electrical devices in these models are presented in the form of planar nonlinear magnetic circuits with lumped elements. The parameters of these elements are determined on the basis of geometric dimensions taking into account the design features of the devices and the physical parameters of the environment.
Аналіз магнітних полів електротехнічних пристроїв на підставі їх колових моделей
Keywords: electric machine; transformer; mathematical model; magnetic circuit; magnetic field; magnetic field induction